Analysis Of The Value Of Time And Patience In Surah Al-'Asr As The Basis For Developing Teachers' Pedagogic Competencies In Fostering Students' Adaptability Character In The Era Of Digital Change - Fadllurrahman; Ihsan Pratama, Arizqi; Siregar, Pahri; Harahap, Nahriyah (Rayah Al-Islam, 2025)
This study aims to analyze the role of the value of time and patience in Surah Al-'Asr as the basis for developing teachers' pedagogic competencies in shaping the adaptability character of students in the digital era. In the context of modern education, rapid technological changes demand students to have high adaptability and flexibility. Therefore, the Islamic values contained in Surah Al-'Asr can be used as a guideline in shaping the character of resilient and resilient students. The research method used is a qualitative study with document analysis of various literature sources, including classical and contemporary interpretations as well as the latest research on character education and modern pedagogy. Data analysis techniques are carried out through identification, reduction, and interpretation of documents to find the relevance of time and patience values to teachers' pedagogic competence. The results showed that the value of appreciation for time helped students in developing discipline, planning, and efficiency in learning, while the value of patience formed mental and emotional resilience in facing academic and social challenges. Teachers with good pedagogic competence are able to integrate these two values in learning methods, such as through time management-based assignments and challenge-based learning that instills perseverance. The conclusion of this study confirms that the application of the value of time and patience in the educational process can increase students' discipline and creativity, forming a more adaptive and flexible character. The relevance of this research to education today is very significant, considering that the challenges of globalization and digitalization require students to have a strong character in facing the dynamics of change. The integration of Islamic values in modern pedagogy can be a solution in building a generation that is not only academically intelligent, but also has moral and spiritual resilience.